KETERLIBATAN SISWA MELALUI PEMBUATAN ECOBRICK SEBAGAI MEDIA PEMBELAJARAN TERINTERNALISASI P5 DI SD NEGERI 2 SANGGRAHAN - Niken; Mukodi, Mukodi; Tisngati, Urip (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to describe and analyze student engagement, impacts, and obstacles in the implementation of ecobrick-making activities within the Projek Penguatan Profil Pelajar Pancasila at SD Negeri 2 Sanggrahan. This research employed a descriptive qualitative approach, involving fourteen fourth-grade students and one classroom teacher as informants, selected through purposive sampling. Data were collected through observation, interviews, questionnaires, and documentation. Data analysis followed the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing, and was processed using Atlas.ti 9 software through data input, coding, data exploration, visualization, and presentation. The results indicate that: (1) student engagement in ecobrick-making activities was good, as reflected in cognitive, behavioral, and emotional aspects; (2) the ecobrick-making activities had a positive impact on students’ character development, particularly in terms of moral concepts, moral attitudes, and moral behavior; and (3) obstacles in implementing ecobrick-making activities were influenced by both internal and external factors.